2016
DOI: 10.1002/biot.201600040
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐stabilizing and cell‐penetrating properties of α‐helix domain of 30Kc19 protein

Abstract: The protein‐stabilizing and cell‐penetrating activities of Bombyx mori 30Kc19 α‐helix domain (30Kc19α) are investigated. Recently, 30Kc19 protein has been studied extensively as it has both protein‐stabilizing and cell‐penetrating properties. However, it is unknown which part of 30Kc19 is responsible for those properties. 30Kc19 protein is composed of two distinct domains, an α‐helix N‐terminal domain (30Kc19α) and a β‐trefoil C‐terminal domain (30Kc19β). The authors construct and produce truncated forms of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…2, 5 and 11), and a straightforward correlation between the parameters of sgRNAs (e.g., GC content or target site location, Supplementary Table 2) and their gene activation efficiencies has not been established. Meanwhile, since dCas9-TV is prone to protein degradation due to its high sequence repetition, future studies will address the possibility whether genetic fusion of XTEN 26 , 30Kc19α 27 or other protein-stabilizing polypeptides to the N- or C-terminus of dCas9-TV may mitigate its degradation issue and further potentiate the dCas9-TV-mediated transcriptional activation.…”
mentioning
confidence: 99%
“…2, 5 and 11), and a straightforward correlation between the parameters of sgRNAs (e.g., GC content or target site location, Supplementary Table 2) and their gene activation efficiencies has not been established. Meanwhile, since dCas9-TV is prone to protein degradation due to its high sequence repetition, future studies will address the possibility whether genetic fusion of XTEN 26 , 30Kc19α 27 or other protein-stabilizing polypeptides to the N- or C-terminus of dCas9-TV may mitigate its degradation issue and further potentiate the dCas9-TV-mediated transcriptional activation.…”
mentioning
confidence: 99%
“…The 30Kc19 protein consists of six alpha-helixes of the N-terminal domain and 12 beta-strands of the C-terminal domain [ 85 ]. The CPP Pep-c19 is located in the α-helix domain [ 84 , 86 ]. Lee et al conducted a study to deliver β-galactosidase (β-gal) into cells using 30Kc19 protein nanoparticles [ 84 ].…”
Section: Types Of Proteins Used To Produce Protein Nanoparticlesmentioning
confidence: 99%
“…The 30Kc19α and 30Kc19 genes were cloned and inserted into a pET-23a expression plasmid vector (Novagen, Madison, WI, USA) using the EcoRI and XhoI restriction enzyme sites, respectively, as described in previous studies [24,28]. The E. coli BL21 strain (DE3, Enzynomics, Daejeon, Korea) was then transformed with the recombinant plasmid and cultivated exponentially in Luria-Bertani (LB) broth medium until O.D.…”
Section: Plasmid Construction and Production Of Recombinant Protein I...mentioning
confidence: 99%
“…These findings suggest that the enhanced EPO productivity in recombinant CHO cells after the intracellular delivery of the 30Kc19 protein is due to the stabilization of mitochondrial enzyme complexes responsible for electron transport and ATP generation [27]. Meanwhile, other studies have demonstrated that the α-helix N-terminal domain of 30Kc19 (30Kc19α), dominantly expressed as a soluble form in E. coli, exhibits protein-stabilizing and cell-penetrating effects similar to or higher than the fulllength 30Kc19 protein [28,29]. However, the effect of the 30Kc19α protein on recombinant protein production in CHO cells compared to the effect of the full-length 30Kc19 protein has not yet been reported.…”
Section: Introductionmentioning
confidence: 98%